Autotuning of PID Controllers A Relay Feedback Approach - Yu, Cheng-Ching (Springer London : Imprint: Springer, 2006)
Recognising the benefits of improved control, the second edition of Autotuning of PID Controllers provides simple yet effective methods for improving PID controller performance. The practical issues of controller tuning are examined using numerous worked examples and case studies in association with specially written autotuning MATLAB® programs to bridge the gap between conventional tuning practice and novel autotuning methods. The extensively revised second edition expands and refines on important work in the ubiquitous PID form of control with material covering: • Derivation of analytical expressions for relay feedback responses with tabulated results for easy reference. • The use of shapes of relay responses to generate information for improved closed-loop control and performance assessment. • The applications of autotuning to multiple-model-based cases for handling process nonlinearity. • The use of feedback shapes to generate information for performance assessment. • The impact of imperfect actuators on controller performance. Autotuning of PID Controllers is more than just a monograph, it is an independent learning tool applicable to the work of academic control engineers and of their counterparts in industry looking for more effective process control and automation. Comments on the first edition: This book is written in a way which not only makes it easy to understand but is also useful to those interested in or working with PID controllers. Assembly Automation The book will be useful to manufacturers and users of control equipment, and also to researchers in the field of automatic tuning. Automatica.